(untitled) (Altre Modernità, 2019)
The following paper is the result of two fieldwork experiences: the observation of the progressive loss of the traditional language by the indigenous kichwa group of the Peruvian Amazon forest and my last stay in the city of Donostia-San Sebastián (Euskal Herria). These experiences allowed me to develop some reflections about the contact between these (apparently different) two worlds: the Native Communities of South America and euskaldunak people. Garabide, a basque non-governmental association, is now helping several indigenous communities making up their linguistic and identity recovery process. In this paper I’ll propose the concept of "linguistic utopia": Garabide is offering to the aforementioned communities practical and theoretical tools, obtained from the long and arduous experience of basque linguistic recovery. This case study will serve as a pretext for developing wider considerations around the Basque idiom, understood not only as an expression of an ethnolinguistic and identity movement. The Euskera language is today considered the realization of a shared and concretized utopia that can be "taught" to others.